Comparison of Time Taken to Assess Cognitive Function Using a Fully Immersive and Automated Virtual Reality System vs. the Montreal Cognitive Assessment - Wong, Wei Teen; Tan, Ngiap Chuan; Lim, Jie En; Allen, John Carson; Lee, Wan Sian; Quah, Joanne Hui Min; Paulpandi, Muthulakshmi; Teh, Tuan Ann; Lim, Soon Huat; Malhotra, Rahul (Frontiers in Aging Neuroscience, 2021)
Introduction: Dementia is increasingly prevalent globally. Existing questionnaire-based cognitive assessment tools may not comprehensively assess cognitive function and real-time task-performance across all cognitive domains. CAVIRE (Cognitive Assessment by VIrtual Reality), a fully-immersive virtual reality system incorporating automated audio-visual instructions and a scoring matrix was developed to assess the six cognitive domains, with potential to maintain consistency in execution of the testing environment and possibly time-savings in busy primary care practice. Aims: To compare completion time of the questionnaire-based Montreal Cognitive Assessment (MoCA) and the CAVIRE in cognitively-healthy Asian adults aged between 35 and 74 years, overall, and in and across each 10-year age group (35-44; 45-54; 55-64; 65-74). Methods: A total of 100 participants with a MoCA score of 26 or more were recruited equally into the four 10-year age groups at a primary care clinic in Singapore. Completion time for the MoCA assessment for each participant was recorded. They were assessed using the CAVIRE, comprising 13 segments featuring common everyday activities assessing all six cognitive domains, and the completion time was also recorded through the embedded automated scoring and timing framework. Results: Completion time for CAVIRE as compared to MoCA was significantly (p<0.01) shorter, overall (mean difference: 74.9 (SD) seconds) and in each age group. Younger, versus older, participants completed both the MoCA and CAVIRE tasks in a shorter time. There was a greater variability in the completion time for the MoCA, most markedly in the oldest group, whereas completion time was less variable for the CAVIRE tasks in all age groups, with most consistency in the 45-54 year-age group. Conclusions: We demonstrate almost equivalent completion times for a VR and a questionnaire-based cognition assessment, with inter-age group variation in VR completion time synonymous to that in conventional screening methods. The CAVIRE has the potential to be an alternative screening modality for cognition in the primary care setting.